ANALISIS KUALITAS JALAN REL LINTAS MALANG-BLITAR KM 72+900 S/D 106+000 BERDASARKAN NILAI TRACK QUALITY INDEKS (TQI) - Pinta Prasetya; Ani Tjitra Handayani (Journal of Innovation Research and Knowledge, 2026)
Railroad performance is essential for the comfort, safety, and punctuality of train operations. Changes in the shape/geometry of railway tracks are influenced by passing tonnage, train frequency, or natural events. Damage to the railway track is permitted as long as it does not exceed the specified limits/tolerances and requires maintenance or repair of the railway. The rail quality indicator is obtained from the results of the railway measurement, namely the Track Quality Index (TQI) value. From the TQI value, the parameters of rail track damage are known, so it can be used as a reference for the priority scale for handling maintenance or road repairs. Based on the TQI value on the Malang-Blitar route along km 72+900 to 106+000, the following values ​​were obtained: Category 1 (100 km/hour <V< 120 km/hour) = 9,529 m; Category 2 (80 km/hour <V< 100 km/hour) = 20,442 m; Category 3 (60 km/hour <V< 80 km/hour) = 4,353 m; Category 4 (Max 60 km/hour) = 86 m